CONCEPTIONS OF LITERARY CRITICISM OF YURIY BOIKO-BLOKHYN IN THE INVESTIGATION ABOUT TARAS SHEVCHENKO’S WORKS - Khorob, S. І. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2020)
The article has the investigation of the conceptions of literary criticism of the Ukrainian scientist from diaspora Yuriy Boiko-Blokhyn in his scientific works about the life and creation of Taras Shevchenko. The author made an effort to systematize them, extrapolating his outlook in present-day time.